Implementasi Manajemen Berbasis Sekolah untuk Meningkatkan Mutu Pendidikan di SMA Negeri 1 Sungai Kakap Kabupaten Kubu Raya - Hendra Wahyudin; Usman Radiana; Luhur Wicaksono (Departement of Mathematics Education, 2024)
The implementation of school-based management is expected to enhance the independence of schools in allocating available resources. This study used a descriptive method with a qualitative approach. The subjects were determined using the Purposive Sampling technique. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted using the interactive model by Milles and Huberman. Techniques for checking data validity included source triangulation, technical triangulation, time triangulation, and member checks. The research results are as follows: (1) school-based management planning is carried out by formulating, establishing, and developing the school’s vision, mission, and goals, identifying school needs, and creating a work program, (2) implementation is done by creating an organizational structure, carrying out various school activities according to the school’s work program, and following the principles of independence, partnership, transparency, and accountability, (3) evaluation is conducted by monitoring programs, carrying out school self-evaluation, and assessing the achievement of work programs, (4) supporting factors include complete and adequate facilities and infrastructure, qualified teachers and educational staff, good partnerships with various parties, a unique school culture, and a strong sense of nationalism, (5) inhibiting factors include the lack of water sources in the school environment and the suboptimal empowerment of teachers and educational staff. In conclusion, the implementation of school-based management has improved the quality of education at Senior High School 1 Sungai Kakap, Kubu Raya Regency